2019
DOI: 10.11114/jets.v7i7.4248
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quadriceps Q-Angle Values of Soccer Players and Wrestlers

Abstract: The aim of this study is to compare according to different positions the mean right and left knee Q angle of footballers and wrestlers. In this study, found the female soccer and wrestlers mean age 20.51 ± 3.47 years, height 165.43 ± 4.82 cm, weight 58.23 ± 5.18 kg. Male soccer and wrestlers has with mean age 21.30 ± 3.45 years, height 173.28 ± 5.45 cm, weight 65.66 ± 5.73 kg. One-way ANOVA, Student t, and Duncan post hoc test were used for statistical analysis. In this study, found that the mean right and lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…Comparing the Q-angle of football players and wrestlers, Şen et al. 32 found significant difference between both values, with football players showing lower values among female football players and male wrestlers showing lower values than male football players.…”
Section: Discussionmentioning
confidence: 98%
“…Comparing the Q-angle of football players and wrestlers, Şen et al. 32 found significant difference between both values, with football players showing lower values among female football players and male wrestlers showing lower values than male football players.…”
Section: Discussionmentioning
confidence: 98%
“…Prop- erly causes of reduced Q angle can mention increased strength in the muscles around the knee and the muscles of the femoral abductor. In this regard, Ismaili et al (2009) stated that factors, such as genu valgum, the weakness of the muscles around the knee, and the external rotation of the tibia increase the Q angle [26].…”
Section: Discussionmentioning
confidence: 99%
“…Al-Tarawneh et al who studied healthy Jordanians (Mean age 32.7 ± 10.1) with no ACL injury , showed that the mean Q angle in men and women was 14.40° (± 1.9) and 18.40° (± 1.8) respectively and stated that Q angle can differ from population to population attributing to variations in life styles [22]. Murat Şen et al who studied footballers and wrestlers from Turkey showed mean right and left knee Q angles of male athletes were 15.08° ± 1.79° and 14.49° ± 1.82° in the standing position [23]. Our sample of athletes also showed similar range of mean Q angles.…”
Section: Discussionmentioning
confidence: 99%
“…Then the proximal arm of the goniometer was aligned to the ASIS; the axis at the midpoint of the patella and the distal arm was aligned with the tibial tubercle. The resultant angle formed by the crossing of these two lines was measured (22,23) and recorded to the resolution of the goniometer; i.e. nearest millimeter.…”
Section: Measurement Of the Q Anglementioning
confidence: 99%